The way of integrity : finding the path to your true self - Beck, Martha Nibley, 1962- (The Open Field-Penguin Life, 2021)
"As Martha Beck says in her book, 'Integrity is the cure for psychological suffering. Period.' In 'The Way of Integrity,' Beck presents a four-stage process that anyone can use to find integrity, and with it, a sense of purpose, emotional healing, and a life free of mental suffering. Much of what plagues us--people pleasing, staying in stale relationships, negative habits--all point to what happens when we are out of touch with what truly makes us feel whole. Inspired by 'The Divine Comedy,' Beck uses Dante's classic hero's journey as a framework to break down the process of attaining personal integrity into small, manageable steps. She shows how to read our internal signals that lead us towards our true path, and to recognize what we actually yearn for versus what our culture sells us. With techniques tested on hundreds of her clients, Beck brings her expertise as a social scientist, life coach and human being to help readers to uncover what integrity looks like in their own lives. She takes us on a spiritual adventure that not only will change the direction of our lives, but bring us to a place of genuine happiness"--